I survived the Great Molasses Flood, 1919 - Ball, Georgia; Vega, Karen de la; Tarshis, Lauren (New York, NY : Graphix, an imprint of Scholastic, 2025)
When the massive metal tank filled with sticky brown molasses that rises up over her crowded North End neighborhood explodes, young Carmen must fight for her life, as a tsunami of molasses rushes through the streets.
Based on the novel in the New York Times bestselling series by Lauren Tarshis.
School Library Journal, February 2025
Includes bibliographical references.
3-6
GN540L
Keywords: Floods -- Comic books, strips, etc; Floods -- Juvenile fiction; Industrial accidents -- Comic books, strips, etc; Industrial accidents -- Juvenile fiction; Molasses -- Comic books, strips, etc; Molasses -- Juvenile fiction; Survival -- Comic books, strips, etc; Survival -- Juvenile fiction; Boston (Mass.) -- History -- 1865- -- Comic books, strips, etc; Boston (Mass.) -- History -- 1865- -- Juvenile fiction; Floods -- Fiction; Industrial accidents -- Fiction; Molasses -- Fiction; Survival -- Fiction; Boston (Mass.) -- History -- 1865- -- Fiction; Historical comics; Graphic novel adaptations; Graphic novels; Comics (Graphic works)